The Antitumoral/Antimetastatic Action of the Flavonoid Brachydin A in Metastatic Prostate Tumor Spheroids In Vitro Is Mediated by (Parthanatos) PARP-Related Cell Death - Diego Luis Ribeiro; Katiuska Tuttis; Larissa Cristina Bastos de Oliveira; Juliana Mara Serpeloni; Izabela Natalia Faria Gomes; André van Helvoort Lengert; Cláudia Quintino da Rocha; Rui Manuel Reis; Ilce Mara de Syllos Cólus; Lusânia Maria Greggi Antunes (MDPI AG, 2022)
Metastatic prostate cancer (mPCa) is resistant to several chemotherapeutic agents. Brachydin A (BrA), a glycosylated flavonoid extracted from Fridericia platyphylla, displays a remarkable antitumoral effect against in vitro mPCa cells cultured as bidimensional (2D) monolayers. Considering that three-dimensional (3D) cell cultures provide a more accurate response to chemotherapeutic agents, this study investigated the antiproliferative/antimetastatic effects of BrA and the molecular mechanisms underlying its action in mPCa spheroids (DU145) in vitro. BrA at 60-100 μM was cytotoxic, altered spheroid morphology/volume, and suppressed cell migration and tumor invasiveness. High-content analysis revealed that BrA (60-100 µM) reduced mitochondrial membrane potential and increased apoptosis and necrosis markers, indicating that it triggered cell death mechanisms. Molecular analysis showed that (i) 24-h treatment with BrA (80-100 µM) increased the protein levels of DNA disruption markers (cleaved-PARP and p-γ-H2AX) as well as decreased the protein levels of anti/pro-apoptotic (BCL-2, BAD, and RIP3K) and cell survival markers (p-AKT1 and p-44/42 MAPK); (ii) 72-h treatment with BrA increased the protein levels of effector caspases (CASP3, CASP7, and CASP8) and inflammation markers (NF-kB and TNF-α). Altogether, our results suggest that PARP-mediated cell death (parthanatos) is a potential mechanism of action. In conclusion, BrA confirms its potential as a candidate drug for preclinical studies against mPCa.